Investigation potential of hydrocolloids in meat analogue preparation. (February 2023) - Taghian Dinani, Somayeh; Broekema, Nicole Louise; Boom, Remko; van der Goot, Atze Jan
Abstract: The texture, appearance and juiciness of meat analogues should resemble meat as much as possible to enhance their adoption by consumers. The effects of the addition of different hydrocolloids (xanthan (X), iota-carrageenan (CA), sodium alginate (SA), guar gum (GG), carboxymethyl cellulose (CMC), low acyl gellan gum (GZ), low methylated pectin (P), and locust bean gum (LBG)) at three concentrations (1%, 2% and 3%) were assessed on blends containing pea protein isolate and wheat gluten that were processed using shear cell technology. The addition of X, CMC and GG resulted in a more strongly flow-oriented structure and the formation of fibers compared to materials without any hydrocolloids. However, the water holding capacity, except with X, hardly increased. X also increased the anisotropy index of samples, but it did not improve the tensile stress of products. The addition of GZ resulted in a much larger tensile stress, especially at higher concentrations. Overall, these findings show the great potential of X and GZ hydrocolloids to improve the textural attributes of meat analogues, which will be an important step to make the transition of meat towards meat analogues more pleasant. Graphical abstract: Image 1